India: A Journey Through a Healing Civilization - Shashank Mani; MANI (Shashank) (New Delhi Harper Collins Publishers India, 2007)
The story of an extraordinary emotional adventure...In 1997, on the fiftieth anniversary of India's independence, Shashank Mani, an IIT alumnus, organized a train journey across India. The purpose - to get a sense of how the country had changed in the past fifty years of independence, and what needed to be accomplished in the future. On this twenty-two day journey, in a specially chartered train, were 200 Indians from different walks of life - young men and women whose commitment would help shape the country's future.As they travelled, they discussed among themselves the issues that bothered them as citizens, and possible solutions. They came up with ideas on how best to fight corruption and kindle a new spirit of entrepreneurship. There was a reaffirmation of love for the country, tempered by an awareness of just how much more needed to be done, whether it was in population control or in protecting the environment. In a world suffering the first signs of an 'industrial hangover', the developmental models discovered during the journey offered the participants new and pragmatic alternatives.As India enters its sixtieth year of independence - and as the original 1997 team plans one more ambitious journey across India - this story is a fitting reminder of where we once were and where we need to head.
Keywords: History; Railroad Travel; India